Microsurgical anatomy of middle longitudinal fasciculus - Aydin, Seckin; Esen Aydin, Aysegul (Annals of Medical Research, 2021)
Aim: Middle longitudinal fasciculus (MdLF) is a cortico-cortical association pathway, and originates from the temporal pole, then extends across the superior temporal gyrus and reaches the inferior parietal lobe. The aim of this anatomical study is to delineate the microsurgical anatomy of MdLF using fiber dissection technique.Material and Methods: Four formalin-fixed cadaveric human brains were dissected by Klingler method. A step-by-step dissection was utilized to expose white matter pathways, including MdLF.Results: MdLF consists of three parts: anterior, middle and posterior. The anterior part of MdLF fibers originates from the temporal pole and extends to posterior along the superior temporal gyrus. The middle part of MdLF is extended from the posterior of the Heschl gyrus to the medial of the arcuate fasciculus. The posterior part of MdLF joined the sagittal stratum together with the posterior limb of the internal capsule and inferior frontooccipital fasciculus.Conclusion: MdLF is still being studied in terms of its anatomy and functions. Considering the connections between the cortical areas with well-known functions such as superior temporal gyrus, angular gyrus and superior parietal lobule, it can be asserted that MdLF is associated with language, auditory, visual and cognitive functions.
Keywords: Dissection; middle longitudinal fasciculus; neuroanatomy; white matter